Vibration analysis of rotary cement kiln using finite element method - Basri Hasan; Yani Irsyadi; Teguh Prakoso Akbar (MATEC Web of Conferences, 2017)
In this research, the implementation of shell of kiln problem has been discussed. The results are analysed in detail in this research for fatigue life for the shell of a kiln. In this work, the shell of the kiln has been modelled by Solid Works. This simulation showed how the most relevant aspects of the developed work presented in this paper can contribute to the state-of-the-art of the analysis of fatigue life of rotary cement kiln technique with innovative ideas and strategies. It also reviews that the obtained results achieve the proposed objectives. Based on the FEA the transfer matrices and overall transfer equation are developed to calculate natural frequencies, and response overall motion equation is established for response analysis. Due to the dimensionality of the problem addressed, the research specification has to set limits to the applicability of the research by selecting only mechanical load problems in rotary cement kiln tasks and goal-seeking to predict the fatigue life simulation investigated. From the simulation, model and boundary conditions are defined. Crack growth behaviour in the rotary kiln was predicted.